CHANGING ARTERIAL STIFFNESS GRADIENT BY NITROGLYCERIN AND ITS RELATION TO CENTRAL PRESSURE WAVE ANALYSIS. (June 2018) - Fortier, C.; Hametner, B.; Vandal-Gelinas, G.; Marquis, K.; Wassertheurer, S.; Weber, T.; Mac-Way, F.; Desjardins, M.-P.; Agharazii, M.
Abstract : Objective: We have previously shown that administration of nitroglycerin (NTG) reduced femoral pulse wave velocity without affecting aortic stiffness, which results in an increase in aortic-femoral (AF) PWV ratio (a measure of arterial stiffness gradient). In this study, we examined the impact of post-NTG changes of AF-PWV ratio on wave reflection using wave separation analysis. Design and method: In 20 treated hypertensive subjects with or without kidney disease, carotid-femoral (CFPWV) (aortic) and femoral-distal (FDPWV) were determined as respective measures of aortic and femoral stiffness. Aortic-femoral PWV ratio (AF PWV ratio) was used as a measure of arterial stiffness gradient. Aortic pressure waveform was obtained through generalized transfer function applied to the radial artery pressure waveform after calibration with systolic and diastolic blood pressures (SBP and DBP). Using GEE, we examined the extent of association between changes in aortic-femoral (AF) PWV ratio, and augmentation index (Aix), pressure forward (Pf), pressure backward (Pb) and reflection magnitude (RM). Results: After administration of NTG, SBP and mean BP (area under the curve) decreased (114 ± 19 vs 107 ± 15 and 89 ± 11 vs 85 ± 9 mm Hg, p < 0.01) without changes in DBP. The CFPWV remained unchanged (12.2 ± 2.2 vs 12.3 ± 2.9 m/s), whereas FDPWV decreased (8.7 ± 1.5 vs 7.2 ± 1.1 m/s, p < 0.001). Accordingly, AF PWV ratio increased (1.42 ± 0.25 vs 1.73 ± 0.41). Aix declined as expected (20.1 ± 11.9 vs 7.7 ± 12.8 %, p < 0.001). There was a slight but not statistically significant reduction in Pf (27.7 ± 10.7 vs 25.4 ± 7.9 mmHg, p = 0.068), while Pb decreased (17.2 ± 8.1 vs 13.4 ± 6.6 mmHg), resulting in a reduction in RM from 0.61 ± 0.10 to 0.51 ± 0.13 (p < 0.001). There was a significant association between the extent of changes in AF PWV ratio and changes in Aix (β = −15, p < 0.001), Pb (β = −9.5, p < 0.001) and RM (β = −0.21, p < 0.001). Conclusions: This study shows that alteration of arterial stiffness gradient with nitroglycerin is associated with changes in arterial wave reflection indices.